Media Informasi Animasi 4 Dimensi Halte Transportasi Publik untuk Kenyamanan Masyarakat menggunakan Teknik Motion Planner - Firnas Azamta; Iskandar Fitri; Albaar Rubhasy (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
As we know, there are a lot of public transportation users, especially buses, which are often used in almost all cities around the world. What is our focus this time is bus stops, many of which are abused from their initial function as a place to pick up and drop off passengers, and are very unfit for use. Therefore, a 4D animation information media for public transportation stops was created. This is done to show the public about the convenience of public transportation stops. This utilization also aims to make the bus stop facilities even better and more comfortable according to the needs of prospective passengers. The concept used in this design is "Livability", a word that refers to a good environment for a community to live in. The design results presented in the interior of this waiting facility are to make public transportation users feel safe and comfortable so that people can interact well with each other while waiting for public transportation.